2015
DOI: 10.1002/fuce.201500133
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of Membrane Electrode Assemblies with Asymmetrical GDL Configurations for PEM Fuel Cells

Abstract: Membrane electrode assemblies (MEAs), based on commercial catalyst‐coated membranes combined with various gas diffusion layers (GDLs) on anode and cathode, were studied in terms of their specific advantages for different operations regimes of proton exchange membrane fuel cells (PEMFCs.) It is verified that MEAs with optimized gas diffusion layer designs (backing and micro‐porous layers) on anode and cathode are able to provide improved cell performance combined with a largely reduced sensitivity towards chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 48 publications
0
22
0
Order By: Relevance
“…To efficiently perform the above functions, the GDL is usually wet-proofed [3][4][5][6][7]. Further, it is normally coated with the so-called micro-porous layer (MPL) on the side facing the catalyst layer in order to enhance the electrical contact with the catalyst layer and properly handle the liquid water emerging from the cathode catalyst layer [1][2][9][10]. The MPL is a mixture that typically consists of carbon black and PTFE particles [1,11].…”
Section: Introductionmentioning
confidence: 99%
“…To efficiently perform the above functions, the GDL is usually wet-proofed [3][4][5][6][7]. Further, it is normally coated with the so-called micro-porous layer (MPL) on the side facing the catalyst layer in order to enhance the electrical contact with the catalyst layer and properly handle the liquid water emerging from the cathode catalyst layer [1][2][9][10]. The MPL is a mixture that typically consists of carbon black and PTFE particles [1,11].…”
Section: Introductionmentioning
confidence: 99%
“…In the works of Kannan et al, 21,22 the authors observed that through the application of an MPL with carbon nanofibers the maximum power output of the fuel cell increased by 0.55W/cm 2 compared to the fuel cell with the conventional MPL. Schweiss et al 23,24 reported that compared to a conventional MPL (SGL 25 BC) an MWCNT-doped MPL (SGL 25 BN) exhibited 7.7 times higher gas permeability and resulted in a decrease in ohmic resistance of 9%. Additionally, the MWCNT-doped MPL resulted in a hydrophilic and highly porous MPL that allowed for the effective removal of liquid water from the cathode.…”
mentioning
confidence: 99%
“…19-29 While conventional MPLs consist of carbon black particles and a hydrophobic agent, such as polytetrafluoroethylene (PTFE), recent findings [19][20][21][22][23][24][25][26][27][28][29] suggest that nano carbon additive materials in the MPL can further enhance fuel cell performance. Park et al 19 showed that the adoption of carbon nanofibers and carbon nanotubes (CNT) in the MPL resulted in increased air permeability and enhanced fuel cell performance.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…PEMFC has different ranges of applications like small electric and electronic devices of low to moderate voltage rat, transportation, battery replacement and electric auxiliary systems of power generation.Currently there are many different fuel cell types with diverse design, structure, power capacity and industrial applications with wide range of operating temperature ranges [1][2][3].…”
Section: Introductionmentioning
confidence: 99%